New Concepts of Neutrosophic Crisp Generalized Closed Functions - Ali H. M. Al-Obaidi; Qays Hatem Imran; Murtadha M. Abdulkadhim; Giorgio Nordo (Neutrosophic Sets and Systems)
In this article, new forms of neutrosophic crisp closed functions are delivered which are called neutrosophic crisp generalized semi generalized (𝑔𝑠𝑔) closed functions. Moreover, these forms are reconstructed to acquire new forms of neutrosophic crisp closed functions which are denoted by (𝑔𝑠𝑔 ∗ , 𝑔𝑠𝑔 ∗∗ ). Finally, the corresponding relations of these forms are studied and analyzed by proof some theorems and propositions.